GAMBARAN KUALITAS HIDUP PADA WANITA MENOPAUSE: Description of Quality of Life in Menopausal Women - Yhenti Widjayanti (Jurnal Ilmiah Keperawatan (Scientific Journal of Nursing), 2022)
During menopause there are physical and psychological changes that can reduce quality of life. This study aimed to identify the quality of life of postmenopausal women. Design of this study was descriptive. The subjects of this study were 33 postmenopausal women whom were collected using simple random sampling technique. Variable of this study was quality of life. Data were collected ny WHOQoL questionnaire. The data was analyzed descriptively by the percentage proportion. The results showed that in the physical domain 70% respondents had good quality of life and 30% had moderate, in the psychological domain, 52% respondents had good quality of life and 48% had moderate. In the social domain, the results showed that 73% respondents had good quality of life, 15% had very good quality of life and 12% had moderate quality of life, while in the environmental domain 73%respondents had good quality of life, 19% had very good quality of life and 8% had moderate quality of life. Recommendations for health cadres always motivate menopausal women to actively participate in physical activities such as exercise, religious activities and health counseling. Health cadres are also expected to provide information about women's health during menopause.